Ecofriendly alternative for sustainable management of banded leaf and sheath blight of maize (Zea mays) - KHOKHAR, M K; BISHT, SUNAINA; GOGOI, ROBIN; BISHT, SUNAINA (The Indian Journal of Agricultural Sciences, 2022)
Banded leaf and sheath blight (BLSB) of maize (Zea mays L.) caused by Rhizoctonia solani f. sp. sasakii is one of the most important yield-limiting factors faced by growers in India. Therefore, attempts were made to identify promising suitable bioagents for the management of BLSB of maize. Present study was carried out to check the efficacy of two bioformulations, viz. Pusa Th3 (Trichoderma harzianum) and Pusa Cg2 (Chaetomium globosum) against BLSB in the Vivek QPM-9 cultivar under field conditions during kharif 2018 and 2019 using seven different treatments. All the treatments significantly reduced the disease incidence and contributed higher yield of maize as compared to positive control. The lowest per cent disease index (37.87 and 53.17%) was recorded in case of both seedtreatment and foliar spray with T. harzianum. It gave 40.39% disease control and also increased the yield up to 28.47% over unprotected plot. It was concluded that BLSB disease can be managed by seed treatment with T. harzianum @2 g/kg seed, followed by one spray of T. harzianum @0.1% at 30 days after sowing. Sustainable ecofriendly disease management options identified in the study can help maize growers not only in safeguarding the crop but also increase cost: benefit ratio. In addition, the results indicated that bio formulation of Pusa Th3 can be used to substitute chemical fungicides especially in controlling BLSB